(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article represents the correlation of cognitive processes of memory on the materials of Ukrainian diary discourse. There was revealed the model of memory in accilological aspect and pointed out the place of its localization. There was also analyzed frames and predicates of the memory.